Delta-8 Tetrahydrocannabinol Product Impurities - Colleen L. Ray; Madison P. Bylo; Jonny Pescaglia; James A. Gawenis; C. Michael Greenlief (Molecules, 2022)
Due to increased concerns regarding unidentified impurities in delta-8 tetrahydrocannabinol (Δ-8 THC) consumer products, a study using Nuclear Magnetic Resonance (NMR), high performance liquid chromatography (HPLC), and mass spectrometry (MS) was conducted to further investigate these products. Ten Δ-8 THC products, including distillates and ready to use vaporizer cartridges, were analyzed. The results yield findings that the tested products contain several impurities in concentrations far beyond what is declared on certificates of analysis for these products. As Δ-8 THC is a synthetic product synthesized from cannabidiol (CBD), there are valid concerns regarding the presence of impurities in these products with unknown effects on the human body. Compounding this problem is apparent inadequate testing of these products by producers and independent laboratories.